2018
DOI: 10.2196/10293
|View full text |Cite
|
Sign up to set email alerts
|

INTERGROWTH-21st Gestational Dating and Fetal and Newborn Growth Standards in Peri-Urban Nairobi, Kenya: Quasi-Experimental Implementation Study Protocol

Abstract: BackgroundThe burden of preterm birth, fetal growth impairment, and associated neonatal deaths disproportionately falls on low- and middle-income countries where modern obstetric tools are not available to date pregnancies and monitor fetal growth accurately. The INTERGROWTH-21st gestational dating, fetal growth monitoring, and newborn size at birth standards make this possible.ObjectiveTo scale up the INTERGROWTH-21st standards, it is essential to assess the feasibility and acceptability of their implementati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The results shared in this paper are part of a larger study, which was conducted over two years (March 2016 -March 2018), before (12-month pre-implementation phase) and during (12-month implementation phase) the introduction of the INTERGROWTH-21 st standards [23]. Before implementation of the INTERGROWTH-21 st standards, ultrasounds were not performed routinely and were only administered by an ultrasonographer upon patient request or when clinically indicated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results shared in this paper are part of a larger study, which was conducted over two years (March 2016 -March 2018), before (12-month pre-implementation phase) and during (12-month implementation phase) the introduction of the INTERGROWTH-21 st standards [23]. Before implementation of the INTERGROWTH-21 st standards, ultrasounds were not performed routinely and were only administered by an ultrasonographer upon patient request or when clinically indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Full details of the study design and methods can be found in the protocol paper [23]. Provider experiences, uptake of the standards, and the association between the implementation of the standards and clinical decision-making outcomes are discussed in a separate paper [24].…”
Section: Methodsmentioning
confidence: 99%
“…All fetal growth monitoring scans were performed by the resident expert sonographer. Further details of the study setting, design and description can be found in the study protocol paper [15].…”
Section: Methodsmentioning
confidence: 99%
“…Traditionally, foetal growth has been evaluated by comparing estimated foetal weights with population-based reference curves. Likewise, some recent reports of the INTERGROWTH-21st project recommend using a single standard for both foetal growth and birthweight [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two competing approaches have been proposed for the detection of SGA, including the INTERGROWTH-21st project [ 11 , 13 ] and a customized approach that assumes that one foetal growth standard does not fit all foetuses and has resulted in proposing customized standards [ 14 , 15 ]. In the latter approach, the optimal weight at term for each fetus is estimated using a mathematical model estimated from foetal and maternal anthropometric variables [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%